"Chronic granulomatous invasive fungal rhinosinusitis associated with SARS-CoV-2 infection: A case report". (December 2021) - Treviño-Gonzalez, Jose Luis; Santos-Santillana, Karla Marisol; Maldonado-Chapa, Felix; Morales-Del Angel, Josefina Alejandra; Gomez-Castillo, Paola; Cortes-Ponce, Jose Rosmal
Abstract: Introduction and importance: Granulomatous chronic invasive fungal rhinosinusitis (GCIFR) is a rare entity with scarce cases reported mainly in subtropical areas. Its prevalence among individuals with clinical suspicion of fungal rhinosinusitis has been reported in approximately 20% in subtropical populations, unlike North America with a prevalence of 0.5%. It is typically associated with Aspergillus flavus and the presence of noncaseating granulomas or Langerhans giant cells on histopathologic examination. Case presentation: We describe a case of a patient with clinical history of recent SARS-CoV-2 infection and development of intense cephalalgia, visual impairment, palpebral ptosis, and limitation of extraocular movements. MRI demonstrated the presence of opacification of paranasal sinuses, and a left intraconal abscess. A surgical endoscopic approach was performed and histopathologic examination revealed frontal GCIFR and maxillary fungus ball. Treatment with IV azoles provided adequate clinical response. Clinical discussion: The spectrum of the fungal rhinosinusitis disease is not clear. However, non-invasive fungal rhinosinusitis is not often found concomitantly with invasive types. GCIFR typically manifests with an indolent and gradual progression at early stages. Advanced stages can exhibit orbital and intracranial involvement leading to visual impairment, frequent relapses, and a poor prognosis. A higher incidence of invasive fungal rhinosinusitis has been reported in patients with SARS-CoV-2 infection despite an unremarkable medical history, associated with immune dysregulation. Conclusion: GCIFR is a rare condition with few cases reported in America. Because of its uncommonness, its diagnosis is often delayed leading to increased morbidity and mortality. Highlights: Granulomatous chronic invasive fungal rhinosinusitis is a rare entity with scarce cases reported. Non-invasive fungal rhinosinusitis is not often found concomitantly with invasive types. A higher incidence of invasive fungal rhinosinusitis is observed in SARS-CoV-2 infection. Early diagnosis of fungal rhinosinusitis is essential due to possibly fatal outcome. Physicians should be aware of atypical manifestations for a prompt diagnosis.